Determination of genotoxic and antigenotoxic properties of essential oil from Ferula orientalis L. using Ames/Salmonella and E. coli WP2 bacterial test systems. (September 2014) - Ozkan, Hakan; Yanmis, Derya; Karadayi, Mehmet; Bal, Tugba; Baris, Ozlem; Gulluce, Medine
The essential oils having many application fields such as medicine, flavoring, cosmetics are natural products obtained from aromatic plants. As the natural products of Ferula species have a wide range of use in folk medicine, this study was planned to evaluate the mutagenic and antimutagenic activities of essential oils of leaves and flowers of Ferula orientalis grown in Erzurum, through the bacterial reverse mutation assay. Furthermore, the chemical compositions of essential oils isolated by the hyrodistillation method were analysed by gas chromatography (GC) and gas chromatography–mass spectroscopy (GC-MS), as their biological activities were connected to their contents. According to our results, any tested essential oil at any used concentration on Salmonella typhimurium TA1535 and TA1537 strains and in Escherichia coli WP2 uvr A strain showed no mutagenic activity. However, the tested materials at different concentrations showed antimutagenic activities against the used mutagens. The inhibition rates ranged against sodium azide (NaN3 ) on S. typhimurium TA1535 from 29% to 36%, against 9-aminoacridine (9-AA) on S. typhimurium TA1537 from 40% to 68% and against N -methyl- N' -nitro- N -nitrosoguanidine (MNNG) on E. coli WP2 uvr A from 23% to 52%, respectively. Also, it is revealed by GC and GC/MS analysis of the essential oils isolated from the leaves and flowers, respectively. The major compounds in these oils were determined as α-cadinol, δ-cadinene and germacrene D-4-ol. The results of this study indicate that as the essential oils of F. orientalis have many constituents, they show no mutagenic activity but significant antimutagenic activity, and these materials can be safely used in medicinal applications after further investigations.